2014
DOI: 10.1063/1.4854915
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Er doping on the structural and magnetic properties of cobalt-ferrite

Abstract: Nanocrystalline particulates of Er doped cobalt-ferrites CoFe(2−x)ErxO4 (0 ≤ x ≤ 0.04), were synthesized, using sol-gel assisted autocombustion method. Co-, Fe-, and Er- nitrates were the oxidizers, and malic acid served as a fuel and chelating agent. Calcination (400–600 °C for 4 h) of the precursor powders was followed by sintering (1000 °C for 4 h) and structural and magnetic characterization. X-ray diffraction confirmed the formation of single phase of spinel for the compositions x = 0, 0.01, and 0.02; and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(51 citation statements)
references
References 14 publications
3
47
1
Order By: Relevance
“…Bands above 600 cm -1 in the spectra of all nanoparticles, appear due to A 1g symmetry involving symmetric stretching of oxygen atom with respect to metal ion at the tetrahedral site. Low frequency phonon modes, E g and 3F 2g in the spectra correspond to the symmetric and anti-symmetric bending of metal-oxygen bond at octahedral sites [6,[17][18][19]. Thus presence of bands at ~302, 467, 593 and 681 cm -1 reflect E g , F 2g (2), (1) concentration.…”
Section: Raman Studymentioning
confidence: 93%
See 1 more Smart Citation
“…Bands above 600 cm -1 in the spectra of all nanoparticles, appear due to A 1g symmetry involving symmetric stretching of oxygen atom with respect to metal ion at the tetrahedral site. Low frequency phonon modes, E g and 3F 2g in the spectra correspond to the symmetric and anti-symmetric bending of metal-oxygen bond at octahedral sites [6,[17][18][19]. Thus presence of bands at ~302, 467, 593 and 681 cm -1 reflect E g , F 2g (2), (1) concentration.…”
Section: Raman Studymentioning
confidence: 93%
“…Bands corresponding to these modes generally appear in the range of 200 to 1200 cm -1 [17][18][19]. Hence, Raman spectra of Dy 3+ doped cobalt ferrite nanoparticles were recorded in the range of 200 to 1200 cm -1 and are shown in Fig.…”
Section: Raman Studymentioning
confidence: 99%
“…The temperature dependence of magnetization studies of gallium (Ga)-substituted cobalt ferrite (CoGa x Fe 2−x O 4 ) revealed the magnetization increase for lower Ga 3+ content (x=0.2 and 0.4) when compared to pure CFO at low temperature and as the temperature increased from 10 K to 400 K magnetization decreased (x=0.4) [23]. Negligible room temperature magnetization with more than two-fold increase in coercivity [~29 kA/m for x=0 to ~66 kA/m for x=0.02] was reported for Er-doped cobalt-ferrite nanocrystals by a sol-gel assisted auto combustion method because of their low magneticordering temperature (<90K) [24]. Substitution of Gd 3+ and Nd 3+ for Fe 3+ induces a decrease in the saturation magnetization and Curie temperature of the nickel ferrite [20].…”
Section: Introductionmentioning
confidence: 94%
“…36 It should be noted that magnetic properties of cobalt ferrite have direct dependent on the morphology, size, and particles purity which strongly are affected by primary parameters in producing route. Hence, several studies are carried out on the sol-gel and autocombustion synthesis of CoFe 2 O 4 using various agents such as citric acid, 11,13,[37][38][39][40][41] glycine, [41][42][43][44][45][46][47][48] urea, 13,41,49,50 hexamine, 51 glucose, 9 polyvinyl alcohol (PVA), 52,53 ethylene glycol (EG), 40,54 malic acid, 55 hexamethylenetetramine (HMT), 43 oxalyl dihydrazide (ODH), 49,56 thiourea, 50 and sago starch. 57 But, it is noted that with regard to biomedical applications of these NPs, the use of organic materials can be inappropriate.…”
Section: Introductionmentioning
confidence: 99%